Circulating vitamin C and digestive system cancers: Mendelian randomization study. Issue 9 (September 2022) - Larsson, Susanna C.; Mason, Amy M.; Vithayathil, Mathew; Carter, Paul; Kar, Siddhartha; Zheng, Ju-Sheng; Burgess, Stephen
Summary: Background & aims: Vitamin C is an antioxidant with a potential role in the prevention of digestive system cancers, but there is yet no consensus whether vitamin C has a causal role in these cancers. The aim of this study was to utilize Mendelian randomization to decipher the potential causal associations of vitamin C with risk of digestive system cancers. Methods: Ten genetic variants previously found to be significantly associated with circulating vitamin C were used as instrumental variables. Effect size estimates for the genetic associations of the vitamin C-associated genetic variants with six major malignancies of digestive system were obtained from the FinnGen (N = 309 154) and UK Biobank (N = 367 542) studies. Results from the two studies were combined using meta-analysis. Results: Genetically predicted higher circulating vitamin C showed a suggestive association with lower risk of small intestine and colorectal cancer after accounting for multiple testing. The odds ratio per 1 standard deviation increment in circulating vitamin C was 0.55 (95% confidence interval 0.32–0.94; P = 0.029) for small intestine cancer and 0.84 (95% confidence interval 0.73–0.96; P = 0.013) for colorectal cancer. There was a suggestive association between genetically predicted higher circulating vitamin C with lower risk of liver cancer in FinnGen but no association in the meta-analysis (odds ratio 0.69; 95% CI 0.36–1.32; P = 0.265). Genetically predicted circulating vitamin C was not associated with cancers of the esophagus, stomach, or pancreas. Conclusion: This Mendelian randomization study indicates that vitamin C might play a role in the prevention of small intestine and colorectal cancer.